Theoretical Substruction of Wiener and Dodd’s Theory of Illness Trajectory in Patients with Liver Cirrhosis - Kim, Hyemin (Advances in Social Sciences Research Journal, 2025)
This study applied Wiener and Dodd’s Theory of Illness Trajectory to patients with liver cirrhosis using a theoretical substruction approach. The purpose was to examine how the theory operates within the context of liver cirrhosis, assess its applicability, and identify areas in which theoretical refinement may be warranted. Through theoretical substruction, the original theory was reorganized into four major concepts—uncertainty, disruption in the illness trajectory, coping with uncertainty, and reconstruction of life. Seven variables were subsequently derived and operationalized using validated empirical indicators appropriate for chronic illness populations. The analysis revealed that patients with liver cirrhosis experience profound uncertainty across physical, identity-related, and temporal dimensions. This multidimensional uncertainty contributes to a perceived loss of control, resulting in disruptions in the expected trajectory of life. Coping with uncertainty involves engaging in uncertainty abatement work and interacting with family, healthcare providers, and broader support networks. Over time, these processes support patients in integrating illness into everyday life and reconstructing a renewed sense of continuity and meaning. Overall, the findings suggest that Wiener and Dodd’s theory is generally applicable to the chronic illness experience; however, certain aspects may require adaptation to adequately reflect the unique physiological and psychosocial characteristics of liver cirrhosis. This theoretical evaluation offers direction for future research aimed at refining and extending the Illness Trajectory Theory to broader chronic illness contexts.